Estrogenic Effects of Pueraria mirifica on the Menstrual Cycle and Hormone-Related Ovarian Functions in Cyclic Female Cynomolgus Monkeys - Hataitip Trisomboon; Suchinda Malaivijitnond; Gen Watanabe; Kazuyoshi Taya (Elsevier, 2004)
This study investigated the estrogenic effect of Pueraria mirifica (P. mirifica) on menstrual cycle length and hormone-related ovarian function. Nine normal cyclic monkeys (Macaca fascicularis) were separated into 3 groups; each group was force fed with a single dose of 10, 100, and 1,000 mg of P. mirifica. The experimental schedule was separated into the pre-treatment and post-treatment periods. Blood samples were collected on days 3, 9 - 14, 19, 24, 29, and every 10 days until the next menstruation for one and two menstrual cycles during two consecutive periods and assayed for serum levels of gonadotropins and ovarian hormones. The result showed a significant increase in lengths of the follicular phase and total menstrual cycle in monkeys treated with 1,000 mg of P. mirifica, but no change in menstrual cycle length in monkeys treated with 10 and 100 mg of P. mirifica. Serum levels of follicle stimulating hormone, luteinizing hormone, estradiol, progesterone, or immunoreactive-inhibin did not change during the first and second menstrual cycles of the post-treatment period for all monkey groups. Our findings demonstrate that although changes in hormonal levels could not be observed in this study, a single dose of 1,000 mg of P. mirifica can disturb ovarian function and menstrual cycle in monkeys. Keywords:: Pueraria mirifica, phytoestrogen, monkey, reproductive hormone, menstrual cycle